The Influence of Personal Characteristics and Subjective Norms on Whistleblowing Intentions With Religiosity as a Moderating Variable - Pratama, Juan Ferdinand Aditya (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2024)
Humans in a workplace can develop work attitudes influenced by both internal and external factors. From these two factors, individuals make decisions that can be right or wrong, and one of the wrong decisions is engaging in fraud or dishonesty. In the case of fraud, there is a form of internal control system, namely the implementation of whistleblowing as a way to prevent fraudulent activities. This study aims to examine the influence of attitudes, subjective norms, perceived behavioral control ( Theory of Planned Behavior ), and self - efficacy on whistleblowing intention, with religiosity as a moderating variable. This research employs a quantitative analysis approach using Partial Least Squares (PLS) on Accounting students from the Faculty of Economics and Business at UNIKA Semarang, class of 2019 - 2022. Several findings revealed the characteristics of attitude, subjective norms, and self - efficacy. Keywords: Fraud, Theory of Planned Behavior, SelfEfficacy, Whistleblowing, Religiosity JEL Code: D42, D40, D51